A new species and first record of Gabunillo Schmalfuss & Ferrara, 1983 (Isopoda, Oniscidea, Armadillidae) from the Neotropics - Souza, Leila A.; Senna, André R.; Kury, Adriano B. (Zootaxa, 2010)
A new species of terrestrial isopod, Gabunillo aridicola sp. nov., is described from Ceará and Rio Grande do Norte States, in Karstic formations in the Brazilian semi-arid (caatinga). This genus, hitherto monotypic, was known only from Gabon. This occurrence is remarkable because very few genera of Armadillidae are known from both Afrotropics and Neotropics, and because it offers evidence of a tropical Gondwana biogeographical component.